Procedural Treatment of Accused People of Determination in the UAE Legislation a Comparative Study - Barakat, Yaman; Monajjed, Manal (Journal of Legal Sciences, 2026)
This study emphasizes the procedural aspect of criminal law as today's defendants are people of determination. This matter prompts us to make some amendments to the procedural laws if a person of determination commits a crime and appears before the court. As a result of this amendment, many services must be available to him during the criminal case without affecting the process, including health services that must be available during the criminal case.There is a problematic aspect to this research; legislation of The United Arab Emirates does not provide special procedural treatment for people of determination.Comparative legislation, such as American law, differs greatly leading the accused people to have many facilities during both investigation and trial.To clarify this, in this research, we have dealt with the treatment of the accused people of determination in the stage of inference, preliminary investigation, and we have reviewed how to try the accused of people of determination.We concluded that there is a legislative shortcoming in the issue of procedural treatment of the accused people of determination, and the need to issue special legislation stipulating the special procedural treatment of the accused people of determination at all stages of the criminal case.